The Effectiveness of Problem-Based Learning in Improving Students’ Writing Descriptive Text in Vocational School - Rindi Dwi Amalia; Rusfandi Rusfandi (Jurnal Inspirasi Pendidikan, 2020)
One of the problems in teaching English to students in vocational high schools is how to make the students more active, creative, and critical. An alternative teaching method that can be used by teachers is Problem-Based Learning (PBL). The objective of this study is to investigate whether the use of PBL provides a significant effect on the students’ writing descriptive text. This study used a quasi-experimental design which was conducted at a vocational school in Malang. The participants of this study were class X Office Administration 1 as the experimental group consisting of 23 students and class X Office Administration 3 as the control group consisting of 23 students. The researcher gave pre-test and post-test and compared the participants’ writing scores in the control and experimental groups by using an independent sample t-test. The result of the post-test indicates that the students in the experimental group achieved a higher mean score than those in the control group on writing descriptive text. The statistical analysis reports that there was a significant difference in scores between the two groups (t = 6.99, p < 0.05). This finding indicates that PBL can be an effective method for teachers in teaching writing descriptive text.